Comparative effectiveness of single versus multiple tablet antiretroviral therapy regimens in clinical HIV practice. Issue 14 (April 2017) - Drozd, Daniel R.; Saag, Michael S.; Westfall, Andrew O.; Mathews, William Chris; Haubrich, Richard; Boswell, Stephen L.; Cole, Stephen R.; Porter, Donna; Kitahata, Mari M.; Juday, Timothy; Rosenblatt, Lisa
Abstract : Abstract: We determined risk of virologic failure (VF) in individuals initiating tenofovir/emtricitabine/efavirenz as single versus multiple tablet regimens (MTR). We found no significant difference in the risk of VF, though did observe a trend toward more VF and M184 V mutations among persons initiating MTR. Temporal trends in care may have confounded results. Abstract : Supplemental Digital Content is available in the text